Does stock influencer on social media and financial well-being affect the stock market participation of the young generations during the Covid-19 pandemic? - Yunita Wijaya Handranata; Muhtosim Arief; Dezie Leonarda Warganegara; Mohammad Hamsal (Global Business & Finance Review (GBFR), 2022)
Purpose: This research aims to study whether there is a relationship between stock influencers and financial well-being on stock market participation. Design/methodology/approach: The research method used in this research is quantitative, with 184 respondents spread over six major islands in Indonesia. The data is processed with SmartPLS 3.0 software. Findings: The study results show a positive and significant influence between stock influencers and financial well-being on stock market participation mediated by intention to invest. However, the direct relationship between stock influencers and financial well-being to stock market participation was found to have no effect. Research limitations/implications: This research contributes to the development of financial studies related to capital market participation in Indonesia which is still very limited. The government needs to pay attention to stock influencers and financial well-being, which can significantly impact stock market participation. Socialization and education programs can be carried out informally in collaboration with influencers and focus on increasing knowledge about stocks and managing personal and household finances. Originality/value: This study adopts variables to capture new phenomena that occurred during the COVID-19 pandemic.
Keywords: 650; Stock influencer; Social media; Financial well-being; Intention to invest; Stock market participation; Stock influencer; Social media; Financial well-being; Intention to invest; Stock market participation